Study of Ethanol Extract of Karamunting (Rhodomyrtus tomentosa (Aiton) Hassk) as Acid-Base Bioindicator - wiwit, Wiwit; W. M Diah, Anang (Jurnal Akademika Kimia, 2023)
Karamunting or Rhodomyrtus tomentosa (Aiton) Hassk is a fruit that contains anthocyanins. This study aimed to determine the potential of the ethanol extract of this fruit as an acid-base bioindicator. Karamuting fruit was macerated using three solvents (n-hexane, ethyl acetate, and ethanol) for 24 hours. The extract of the karamunting fruit was tested as indicators in acid-base solutions and buffer solutions and compared with phenolphthalein and methyl orange for acid-base titrations, namely: Strong acids with strong bases, weak acids with strong bases and weak bases with strong acids. The results showed that the ethanol extract of karamunting fruit was brown, in strong acids was red, in strong bases was dark green, in weak acids was pink, and in weak bases was light green. Furthermore, the kara munting fruit indicator extract buffer solution gave four groups of colour changes, namely, at pH 1, it was red; at pH 2 to 6, it was pink; at pH 7 to pH 10, it was light green; and at pH 11 to 12, it was dark green. The ethanol extract of karamunting fruit can be used as an acid-base indicator because it gives equivalent results to comparative indicators, namely phenolphthalein and methyl orange.